Analyzing visual data - Ball, Michael S.; Smith, Gregory W. H. (California: Sage Publications, 1992)
Contents: 1.the use of photographs in a discipline of words. 2. analyzing the content of visual representations. 3. symbolist and structuralist analyses of visual experience.
Keywords: Social Sciences